210 Occupational health practices for wastewater treatment workers. (24th April 2018) - Porru, S; Carta, A; Bellina, B; Arici, C
Abstract : Introduction: The increase in the global population entails large production of wastewaters (WW) around the world. WW treatment plants (WWTP) may represent a challenging and hazardous work environment, since various biological agents (viruses, bacteria, fungi, parasites), as well as endotoxins, can be transmitted to the ambient air in WW bioaerosols and cause various disorders. No occupational exposure limit values are currently available. Thus, the potential biohazard (BH) to WWTP workers (WWTPW) has become an increasingly relevant occupational health and safety (OHS) issue. Aims of our contribution are: to provide a state-of-the-art overview on the occupational BH to WWTPW and to elaborate good OHS practices, based on a field study. Methods: Ten-year (2008–2017) scoping review of articles in the PubMed ® database, published in English, French, Italian or Spanish; full text review of the articles. Field study in a sample of 4 WWTP companies managing more than 200 plants overall, with a capacity varying from less than 1000 to more than 8 70 000 population equivalents and employing about 5 to 50 WWTPW. The study entails: collection of OHS documentation on risk assessment and management, health surveillance, education and training; microbiological environmental monitoring (culturable, countable, assayable biological contaminants); investigation on general and specific health data in a sample of WWTPW, by administering a questionnaire regarding socio-demographic aspects, life habits, occupational and clinical history, preventive and protective measures, and by collecting some functional data (e.g. respiratory function); exploring correlations between BH and OHS outcomes among WWTPW. Result: Scoping review is ongoing as well as enrolment of WWTP and occupational data collection. Discussion: Main expected results are: assessment of occupational BH in WWTP; development of good OHS practices, particularly on risk assessment, health surveillance, fitness for work, immunisation and preventive practices in WWTP; generation of benchmarks; contribution to the research on occupational limit values for BH.